Lithological and textural controls of Mississippi Valley type mineralization of mantles in Shalipayco, Junín, Peru - Tuanama Tuanama, Nancy (2021)
The problem to be solved was which types of lithological, textural and structural controls were favorable to the mineralization of the Shalipayco deposit. Geochemical exploration, sedimentological studies, geological mapping, stratigraphic columns and diamond drilling were carried out, furthermore, performing surface and drill core sampling. It was found mineralized mantos of the Shalipayco project are located lithostratigraphically within the rocks of the Pucara Group, specifically in the Chambara Formation with lithological control of the mineralized mantos, they are coarse to medium grained dolomites (wackestone and packstone) present vuggy type porosity, and the most important textures favorable to the mineralization of the mantos are the evaporitic tectonic breccias, evaporitic breccias, crackel breccia, evaporitic pseudobreccias, and porous dolomites where the dissolution cavities are filled by crystallized dolomite and/or Zn and Pb sulfides. Recognized structural control of mineralization are high angle faults, finally, it has been found the following mineralized mantos, Virgencita, Intermedio and Resurgidora with clear typology of being a Mississippi Valley type deposit.